Metatarsophalangeal and Metatarso-Sesamoid Joint Interaction in Hallux Valgus Deformity: A Case- Control Study - Kepler Carvalho MD; Kevin N. Dibbern PhD; Lily G. McGettigan; Andrew Behrens; Nacime SB Mansur MD; Emilio Wagner MD; Pablo Wagner MD; Caio A. Nery MD; Alexandre L. Godoy-Santos MD; Matthieu Lalevée MD; Cesar de Cesar Netto MD, PhD (Foot & Ankle Orthopaedics, 2022)
Category: Bunion; Lesser Toes; Midfoot/Forefoot Introduction/Purpose: Hallux valgus deformity (HVD) is a complex 3D distortion that involves varus, dorsiflexion and pronation of the first metatarsal. Deformity is usually assessed by conventional 2D measurements such as hallux valgus and intermetatarsal angle. Weightbearing CT (WBCT) 3D Distance Mapping (DM) and Coverage Mapping (CM) allow assessment of relative positioning between opposing articular surfaces, providing information in regards to articular coverage and joint subluxation, that can potentially influence development of arthritic degeneration and symptoms, as well as dictate outcomes. The aim of this study was to develop a DM and CM algorithm to assess metatarsophalangeal (MTP) and metatarso-sesamoid (MS) joint interaction in HVD patients and compare it to healthy controls. We hypothesized that significant MTP and MS joints lateral subluxation would be observed. Methods: In this IRB-approved study, we included 9 HVD patients (mean age 37.1y; 6F/3M) and 5 controls (mean age 39y; 4F/1M) that underwent foot WBCT foot. Bone segmentation of WBCT images for the first and second metatarsals, first and second proximal phalanxes as well as tibial and fibular sesamoids was performed using specific software. Joint interaction with DM and CM of the first and second MTP joints, as well as MS joints were calculated. The surface of the MTP joints were divided in a 2x2 grid using principal axes to provide a more detailed analysis. DMs were color coded to facilitate data interpretation (Figure). Blue color represented expected normal joint interaction (distances from 1 to 3 mm), yellow/red color symbolized increased joint distances (distances from 3 to 5 mm) and pink color indicate completely uncovered articular areas (distances >5mm). Comparisons were performed with independent t-tests/Wilcoxon. P values <.05 were considered significant. Results: Examples of coverage maps for an HVD patient and a control are presented in the attached Figure, demonstrating the obvious lateral and dorsal displacement of the distance maps for joint interaction of the first MTP joint, with decreased articular coverage of the medial aspect of the joint. When comparing first MTP joint articular coverage (CMs), HVD patients demonstrated significantly decreased coverage of the dorsomedial quadrant (77%, p=0.0002), and significantly increased coverage of the plantarlateral (182%, p=0.005) and dorsolateral quadrants (44.9%, p=0.035). Findings are consistent with lateral first MTP joint subluxation and dorsiflexion of the first metatarsal. The second MTP joint demonstrated findings consistent with early hammertoe dorsiflexion contracture and dorsolateral joint subluxation, with significantly decreased articular coverage of the plantarmedial quadrant (88%, p=0.01). No significant changes in joint coverage were observed for the MS joints, however a significant widening of the fibular MS joint was noticed (76.7%, p=0.013). Conclusion: In this case-control study, we developed a Distance and Coverage Map WBCT Algorithm to objectively assess 3D joint interaction, articular coverage and subluxation in HVD. We observed significant amount of first and second MTP joint subluxation in HVD patients when compared to controls, with a plantarmedial and dorsolateral direction for respectively the first and second MTP joints. No significant joint subluxation of the metatarso-sesamoid joint was noted. Our hope is that DM and CM can optimize diagnosis, staging, and assessment of treatment and outcomes in hallux valgus and lesser toe deformities. Additional prospective and appropriately sized studies are needed.